2007
DOI: 10.1002/biot.200600232
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of casein by microbial transglutaminase and its resulting influence on the stability of micelle structure

Abstract: The influence of enzymatic crosslinking by microbial transglutaminase (mTG) on the stability of casein micelles of ultrahigh temperature (UHT)-treated milk in the presence of EDTA (0-0.45 mM) or ethanol (0-74 vol%) as well as under high hydrostatic pressures up to 400 MPa was investigated. Disintegration of micelles and changes in micelle size were monitored by the measurement of turbidity as well as by dynamic light scattering. The results show that the incubation of UHTtreated milk with mTG resulted in an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Hydrophobic nutraceuticals, such as curcumin (Sahu et al ., 2008 ), omega-3 fatty acids (Zimet et al ., 2011 ) andvitamin D2 (Semo et al ., 2007 ), can be incorporated into casein micelles. The casein micelle can be further stabilized by cross-linking with transglutaminase (Partschefeld et al ., 2007 ). The enzymatic cross-linking creates nanogel particles that show improved heat stability but lower stability at acidic pH than native casein micelles (Huppertz and de Kruif, 2008 ).…”
Section: Self-assembling Proteins and Peptidesmentioning
confidence: 99%
“…Hydrophobic nutraceuticals, such as curcumin (Sahu et al ., 2008 ), omega-3 fatty acids (Zimet et al ., 2011 ) andvitamin D2 (Semo et al ., 2007 ), can be incorporated into casein micelles. The casein micelle can be further stabilized by cross-linking with transglutaminase (Partschefeld et al ., 2007 ). The enzymatic cross-linking creates nanogel particles that show improved heat stability but lower stability at acidic pH than native casein micelles (Huppertz and de Kruif, 2008 ).…”
Section: Self-assembling Proteins and Peptidesmentioning
confidence: 99%
“…[30] When TGase was used to treat the ultra-high temperature-treated milk, larger hydrodynamic radius and enhanced micellar stability were observed, and formation of intra-micellar iso-peptide bonds in milk proteins was responsible for the enlarged radius. [31] Similarly, both GC-caseinate I and II were crosslinked protein products by TGase with larger hydrodynamic radius and enhanced aggregation than sodium caseinate. GC-caseinate I had slightly larger hydrodynamic radius than GC-caseinate II, because it was much crosslinked during preparation.…”
Section: Other Properties Of Gc-caseinate I and Iimentioning
confidence: 99%
“…It was observed that caseins cross-linked by TGase have better stability in their micellar structure. 10 When caseinate was crosslinked and glucosamine-conjugated under the action of TGase, its emulsifying, foaming and rheological properties were improved. 11 Moreover, a ternary system comprising the three elements horseradish peroxidase (HRP; EC 1.11.1.7), glucose oxidase (EC 1.1.3.4) and D-glucose was also used to induce the crosslinking of several proteins like SPI, caseinate and gelatin.…”
Section: Introductionmentioning
confidence: 99%